Cseresznyelégy elleni védekezés törzsinjektálással - Gyuris, Rita; Sörös, Csilla; Gutermuth , Ádám; Szabó, Árpád (GEORGIKON FOR AGRICULTURE, 2022)
The European cherry fruit fly (Rhagoletis cerasi) can cause up to 100% damage in Hungary and in some other countries. This fly makes the crop completely unusable for export and fresh consumption. Smaller trees can be successfully protected by spraying in the intensive cultivation. But spraying is often applied in unnecessary amounts, what pollutes the environment and most of the spraying does not reach the target pests. Injection affects only tree organisms, environmentally friendly, and we can use low doses of the active ingredient to kill pests. Trunk injection technique is not as widely used in Hungary as spraying. There are a lot of researches in the world based on injecting techniques of fruit trees. In our work, we select and formulate pesticides into injectable formulations, evaluate the experiment from an entomological view, and then measure the active ingredient residue in the fruit, leaves and flower by using the QuEChERS method. In this study we investigated the effect of the trunk injection. When trees were treated with 0.8 g active acetamiprid ingredient, we reached 100% protection against the cherry fruit fly. The insecticidal effect was also lower with lower dose treatments (88%, 94%). Acetamiprid ingredient residue in the cherry crop were ranged from 19.6 ng / g to 57.8 ng / g, depending on the treatment dose.